Biodiversity of insects in the Amazon: Survey of social wasps (Vespidae: Polistinae) in Amazon rainforest areas in Amazonas State, Brazil - Somavilla, Alexandre; Moraes Junior, R. N. M.; Oliveira, Marcio Luiz de; Rafael, José Albertino (Sociobiology, 2020)
The thematic network 'Biodiversity of Insects in the Amazon' is the first network among researchers of the Brazilian Amazon in terms of the increase of knowledge and provision of subsidies for the conservation of Amazonian biodiversity, focusing on insects, aiming as well to disseminate this knowledge to different sectors of society. In this way, expeditions to six localities in the Amazonas State were carried out and we present here the results for social wasps (Vespidae: Polistinae). We used three modified Malaise traps traps from July 2016 to June 2017. A total of 140 species and 20 genera were collected: 92 species and 18 genera in ZF-2- Manaus area, which presented the greatest diversity, followed by Tefé (73 species, 16 genera), Careiro-Castanho (72 species, 17 genera), Novo Airão (71 species, 16 genera), Presidente Figueiredo (62 species, 16 genera), and Ipixuna (58 species, 17 genera). Metapolybia rufata Richards, 1978 and Polybia diguetana du Buysson, 1905 were new records for Brazil, and other six species were first records for Amazonas state. The results indicate that further investigations should significantly increase the knowledge of wasp species diversity in the Amazon region and add more information on Polistinae diversity
Keywords: Agelaia; Polybia; Amazon biome; Entomologists network